Catalogue of socioeconomic disparities and characteristics of 199+ chronic conditions-A nationwide register-based population study. - Michael Falk Hvidberg; Anne Frølich; Sanne Lykke Lundstrøm (PLoS ONE, 2022)
Background Real-world information on socioeconomic differences within and between chronic conditions represents an important data source for treatments and decision-makers executing and prioritising healthcare resources. Aims The aim of this study was to estimate the prevalence and mean of socioeconomic disparities from educational, income, and socioeconomic positions of 199 chronic conditions and disease groups, including sex and age group estimates, for use in planning of care services and prioritisation, by healthcare professionals, decision-makers and researchers. Methods The study population includes all Danish residents 16 years and above, alive on 1 January 2013 (n = 4,555,439). The data was established by linking seven national registers encompassing educational achievements, incomes, socioeconomic positions, hospital- and general practice services, and filled-in out-of-hospital prescriptions. The health register data were used to identify the 199+ chronic conditions. Socioeconomic differences were primarily measured as differences in educational prevalence levels from low to high educational achievements using a ratio. Furthermore, multiple binary logistic regression models were carried out to control for potential confounding and residual correlations of the crude estimates. Results The prevalence of having one or more chronic conditions for patients with no educational achievement was 768 per thousand compared to 601.3 for patients with higher educational achievement (ratio 1.3). Across disease groups, the highest educational differences were found within disease group F-mental and behavioural (ratio 2.5), E-endocrine, nutritional and metabolic disease (ratio 2.4), I-diseases of the circulatory system (ratio 2.1) and, K-diseases of the digestive system (ratio 2.1). The highest educational differences among the 29 common diseases were found among schizophrenia (ratio 5.9), hyperkinetic disorders (ratio 5.2), dementia (ratio 4.9), osteoporosis (ratio 3.9), type 2 diabetes (ratio 3.8), chronic obstructive pulmonary disease COPD (ratio 3.3), heart conditions and stroke (ratios ranging from 2.3-3.1). Conclusions A nationwide catalogue of socioeconomic disparities for 199+ chronic conditions and disease groups is catalogued and provided. The catalogue findings underline a large scope of socioeconomic disparities that exist across most chronic conditions. The data offer essential information on the socioeconomic disparities to inform future socially differentiated treatments, healthcare planning, etiological, economic, and other research areas.